2005
DOI: 10.1002/em.20124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mangiferin on radiation-induced micronucleus formation in cultured human peripheral blood lymphocytes

Abstract: Irradiation causes a variety of lesions in important biomolecules of the cell through generation of free radicals leading to genomic instability. DNA strand breaks, acentric fragments, or defective kinetochores are manifested as micronuclei after the first cell division. Chemicals that can trap free radicals may reduce the deleterious effects of ionizing radiation. Mangiferin (MGN), a glucosylxanthone derived from Mangifera indica (mango), was investigated for its ability to reduce the frequency of radiation-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 58 publications
(53 reference statements)
3
49
0
Order By: Relevance
“…Jagieta and Venkatesha demonstrated that mangiferin scavenges ROS and protects against ultraviolet irradiation-induced OS [27]. Also, Nair and Devi showed that mangiferin has hypolipidemic properties [28]. Although we did not determined the effects of mango extract on serum lipid profiles, even though we have previously shown that Lipofundin induces hyperlipidemia and subse- quently OS [17].…”
Section: Discussionmentioning
confidence: 59%
“…Jagieta and Venkatesha demonstrated that mangiferin scavenges ROS and protects against ultraviolet irradiation-induced OS [27]. Also, Nair and Devi showed that mangiferin has hypolipidemic properties [28]. Although we did not determined the effects of mango extract on serum lipid profiles, even though we have previously shown that Lipofundin induces hyperlipidemia and subse- quently OS [17].…”
Section: Discussionmentioning
confidence: 59%
“…Some of them also reported dose-dependent radioprotective effect. 23,[53][54][55][56][57][58][59] In this study we used the CBMN assay simultaneously with criteria for scoring as suggested by Fenech et al 22) and also obtained interesting results. EEP and quercetin did not cause significant formation of MN, NB and NPB in non-irradiated samples as compared to negative control.…”
Section: Discussionmentioning
confidence: 99%
“…23 Likewise, plant polyphenols such as naringin and mangiferin have been reported to protect mice and HPBLs against radiation-induced MN formation. 43,47 Certain other plant flavonoids, such as luteolin, quercetin, kaempferol, morin, rutin, fisetin, myricetin, epicatechin, genistein, eridictyol, phloretin, naringin, and hesperidin have been found to protect mice bone marrow cells against the radiation-induced micronuclei. 47,54,55 SCE not only protected against the formation of BNC with 1 MN but also with 2 or multiple MNs in the cultured splenocytes after exposure to different doses of γ-radiation, indicating that SCE could efficiently protect complex multiple sites of DNA damage.…”
Section: Discussionmentioning
confidence: 99%